MicroRNA‐337‐3p controls hepatobiliary gene expression and transcriptional dynamics during hepatic cell differentiation. Issue 1 (16th November 2017) - Demarez, Céline; Gérard, Claude; Cordi, Sabine; Poncy, Alexis; Achouri, Younes; Dauguet, Nicolas; Rosa, David A.; Gunning, Patrick T.; Manfroid, Isabelle; Lemaigre, Frédéric P.
Abstract : Transcriptional networks control the differentiation of the hepatocyte and cholangiocyte lineages from embryonic liver progenitor cells and their subsequent maturation to the adult phenotype. However, how relative levels of hepatocyte and cholangiocyte gene expression are determined during differentiation remains poorly understood. Here, we identify microRNA (miR)‐337‐3p as a regulator of liver development. miR‐337‐3p stimulates expression of cholangiocyte genes and represses hepatocyte genes in undifferentiated progenitor cells in vitro and in embryonic mouse livers. Beyond the stage of lineage segregation, miR‐337‐3p controls the transcriptional network dynamics of developing hepatocytes and balances both cholangiocyte populations that constitute the ductal plate. miR‐337‐3p requires Notch and transforming growth factor‐β signaling and exerts a biphasic control on the hepatocyte transcription factor hepatocyte nuclear factor 4α by modulating its activation and repression. With the help of an experimentally validated mathematical model, we show that this biphasic control results from an incoherent feedforward loop between miR‐337‐3p and hepatocyte nuclear factor 4α. Conclusion: Our results identify miR‐337‐3p as a regulator of liver development and highlight how tight quantitative control of hepatic cell differentiation is exerted through specific gene regulatory network motifs. (Hepatology 2018;67:313‐327).